Transformative Leadership in Pesantren Based Vocational Excellence Centers: A Phenomenological Exploration of Principals’ Lived Experiences - Shofiana, Dwi Erma; Imron, Imron; M. Tohirin (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2025)
This study explores the lived experiences of the principal of SMK Syubbanul Wathon in implementing transformative leadership within a pesantren based Vocational Excellence Center (SMK Pusat Keunggulan Berbasis Pesantren). Using a qualitative phenomenological approach, the research investigates how pesantren values such as ta’dzim, amanah, ijtihad, and ikhlas are internalized and practiced in leadership that harmonizes spiritual integrity and managerial effectiveness. Data were collected through in-depth interviews, documentation, and observation, and analyzed thematically to reveal the essence of leadership transformation rooted in pesantren ethics. The findings show that the principal functions as both an institutional leader and a moral guide, translating Islamic values into organizational behavior that promotes participation, innovation, and reflective learning. Transformative leadership at SMK Syubbanul Wathon emerges as a moral and structural process where ethical consciousness directs institutional change. The study highlights how faith based morality interacts with professional demands in shaping educational transformation. It contributes to a broader understanding of Islamic educational leadership by integrating spirituality and transformative leadership theory, positioning pesantren based leadership as a model for sustainable, value driven school management in vocational education reform.